A revisit of farm size and productivity: Empirical evidence from a wide range of farm sizes in Nigeria. (October 2021) - Omotilewa, Oluwatoba J.; Jayne, T.S.; Muyanga, Milu; Aromolaran, Adebayo B.; Liverpool-Tasie, Lenis Saweda O.; Awokuse, Titus
Highlights: Inverse farm size-productivity relationship (IR) has been documented in Africa, but mostly among smallholders. We examine this IR over a wider range of farm sizes and among medium-scale farms (MSF) up to 40 ha in Nigeria. We find a U-shaped relationship with IR existing up to 22 ha (turning point) but productivity increases afterwards. Turning point for farmers who stepped up into MSFs is at 11 ha, in contrast to 22 ha for those who stepped in. Evidence indicates MSFs exhibit heterogeneity in productivity depending on their mode of entry into farming. Abstract: The relationship between farm size and productivity has been studied extensively in the agricultural and development economics literature. However, most of the documented evidence in sub-Saharan Africa (SSA) is based on samples of small-scale farms operating 5 ha or less, with very little evidence assessing this relationship over a wider range of farm sizes. This omission is especially important considering the rapid expansion of medium-scale farms in much of Africa. This study examines the farm size-productivity relationship over a range of farms between zero and 40 ha in Nigeria. It also tests whether there is heterogeneity in productivity within medium-scale farms depending on how they came into being. Using four measures of productivity, empirical estimates reveal a U-shaped relationship where the IR holds between zero and about 22 ha, turning positive afterwards. Moreover, when medium-scale farms are distinguished between those who were actively engaged as small-scale farmers and stepped up/expanded their scale of operation and those who were primarily in non-farm employment and later stepped into medium-scale farming, the turning point for farmers who stepped up into medium-scale farming is at 11 ha, in contrast to 22 ha for those who stepped in. Further evidence suggests heterogeneity in productivity within medium-scale farms depending on whether the owner-operators stepped up or stepped into medium-scale farming. These findings imply that policies facilitating smallholders' ability to expand the scale of their activities could contribute substantially to growth in farm productivity, agricultural commercialization and increase in food security in Nigeria, although in most areas only a small proportion of smallholder households are in a position to do this.